Pengaruh Pengendalian Ketersediaan Stok dan Distribusi terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan Toko Bangunan - Jamaludin Goleng; Aswin Naldi Sahim; Widya Ningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Building Stores are now in a fairly tight competitive environment, where consumers have the freedom to choose a store according to their needs and budget. Customer loyalty is very important for the sustainability of Building Stores. The main objective of this study is to study the Loyalty of building store customers which is assumed to be influenced by two main factors, namely stock control and distribution. Stock control aims to maintain the availability of goods according to needs, while distribution regulates the flow of goods from producers to consumers. Customer satisfaction is a mediator variable that can strengthen the relationship between stock and distribution on loyalty. The research method uses a descriptive quantitative approach with a survey of 84 customers selected by random sampling. The instrument was measured using a five-point Likert scale and the SmartPLS SEM statistical data analysis process. The results of the study indicate that Consumer Satisfaction has a direct and significant effect on customer loyalty, while stock and distribution control does not have a direct and significant effect on customer loyalty. However, stock and distribution control has an indirect effect on customer loyalty in building stores, namely through customer satisfaction. Thus, customer satisfaction has a very large role in building customer loyalty because it is a Full Mediator Variable for the relationship between stock and distribution control and Customer Loyalty. The results of the study indicate that the research model can be used to study issues about Customer Loyalty in building stores. Furthermore, this information can be used to design and implement practices in building loyalty in building stores.